Origins of the hydrogen bound to carbon 1 of glucose in fasting: significance in gluconeogenesis quantitation - Chandramouli, V; Ekberg, K; Schumann, W.C; Wahren, J; Landau, B.R (American journal of physiology: endocrinology and metabolism, 1999)
Departments of Medicine and Biochemistry, Case Western Reserve University School of Medicine, Cleveland, Ohio 44106; and Division of Clinical Physiology, Karolinska Hospital, S-171 76 Stockholm, Sweden Healthy subjects ingested 2 H 2 O. 2 H enriched the hydrogen bound to carbon 1 of blood glucose 1.3 to 1.8 times more than the hydrogens bound to carbon 6. Enrichment at carbon 1 was more than at carbon 5 after 14 h, but not after 42 h, of fasting. After overnight fasting, when [2,3- 3 H]succinate was infused, 34 times as much 3 H was bound to carbon 6 as to carbon 1. On [1- 2 H,1- 3 H,1- 14 C]galactose infusion, the ratios of 2 H to 14 C and of 3 H to 14 C in blood glucose were 30% less than in the galactose. 3 H at carbon 6 was 1% of that at carbon 1 of the glucose. Thus, although the two hydrogens bound to carbon 1 and the two bound to carbon 6 of fructose 6-phosphate ( p ) during gluconeogenesis are equally enriched in 2 H via pyruvate's equilibration with alanine, one of each is further enriched via hydration of fumarate that is converted to glucose. That hydrogen at carbon 1 of fructose 6-phosphate ( P ) is also enriched in fructose 6- P 's equilibration with mannose 6- P . 2 H from 2 H 2 O at carbon 1 to carbon 2 of blood glucose cannot then quantitate gluconeogenesis because of [1- 2 H]glucose formation during glycogenolysis. Triose-P cycling has a minimal effect on quantitation. 2 H recovery in glucose from [1- 2 H]galactose does not quantitate galactose conversion via UDP-glucose to glycogen. deuterium oxide; galactose; succinate; glycogenolysis